Catalytic conversion of ethanol to hydrocarbons - V. F. Tretyakov; Y. I. Makarf; R. M. Talyshinsky; N. A. Frantsuzova; V. N. Torhovsky; S. N. Antonuk; K. V. Tretyakov (Тонкие химические технологии, 2010)
The fundamentals of catalytic bioethanol conversion into gasoline products, ethylene and aromatic hydrocarbons are studied. New catalysts on the basis of HZSM-5 are synthesized for these purposes. The scheme of the mechanism of process key stages is offered. The possibility of catalytic hydrogenation of mixture of aromatic hydrocarbons contained in products of bioethanol conversion into motor fuel is demonstrated.